The Mediating Role of Electronic Trust and the Moderating effect of Customer Oriented and Innovativeness on the influence of Electronic Service Quality towards Electronic Satisfaction of Electronic Banking Users in Thailand - Thongkhum, Pichet; Wingwon, Boonthawan; Piriyakul, Montree (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2022)
The purpose of this research were to study (1) the importance of e-service quality, e-trust, e-satisfaction, customer oriented, and innovativeness, (2) to study that e-trust as a mediating role that transfers the influence of e-service quality to e-satisfaction, (3) and to study the moderating effect of customer oriented and innovativeness under conditions of variable levels in the relationship of e-trust as a mediating role that transfers the influence of e-service quality to e-satisfaction. The sample group was 820 electronic banking users in Thailand. The tool was a questionnaire. The data were analyzed by using descriptive statistics to determine the frequency values, percentage, mean, and standard deviation. The inferential statistics were used to analyze data with a structural equation model (SEM) by ADANCO and PROCESS program. The results showed that all factors were at a high level. However, the levels were descending in descendent order: e-satisfaction, e-service quality, e-trust, innovativeness, and customer oriented. E-trust is a key factor in transferring the influence of e-service quality to e-satisfaction well both before and after directing relationships through customer oriented and innovativeness. All Hypotheses were supported. Therefore, Banks should focus on customer oriented and innovativeness at a low to moderate level because the high-level are not positive impact for the consumer's e-satisfaction. The whole result can be the guidelines to generate the issues of service quality, trust, satisfaction, customer oriented, and innovativeness in electronic banking users in Thailand in order to strengthen the major role of competitive advantage in the organization. Moreover, it should be the important policy to be transferred as the best practice of organization.